Preparation and application of chitosan modified polymethacrylate
Through the preparation and application of chitosan-modified polymethacrylate materials, the problem of removing doxorubicin in wastewater is solved, and the effect of efficient adsorption and bioenvironmental protection is achieved, which significantly improves the removal rate of doxorubicin.
Patent Information
- Application Number
- CN202411599822.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-11
- Publication Date
- 2025-01-14
AI Technical Summary
The prior art is difficult to effectively remove the anti-tumor drug doxorubicin from wastewater, and its release poses a threat to the environment and human health.
The chitosan-modified polymethacrylate material is heated by mixing methacrylic monomers, crosslinking agents, initiators and pore-forming agents to form a composite material and mix it with chitosan to improve adsorption performance. adsorbent in water.
The adsorption rate of doxorubicin is significantly improved to reach more than 45%, effectively removing doxorubicin from wastewater, and has good biocompatibility and renewability.
Smart Images

Figure CN119303555A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the preparation and application of a polymer adsorption material, and in particular to the preparation of chitosan-modified polymethacrylate and the application of the chitosan-modified polymethacrylate in the adsorption of anti-tumor drugs. Background Art
[0002] Doxorubicin (DOX), also known as doxorubicin, is an anthracycline antitumor antibiotic. DOX is used in the clinical treatment of various malignant tumors and has significant antitumor effects. Its mechanism of action is to inhibit the synthesis of nucleic acid, the genetic material of cancer cells. But at the same time, it has extremely strong cytotoxicity. Once DOX is released into the water, it will have a considerable impact on the ecological environment and cause certain harm to human health.
[0003] The main technologies for dealing with antibiotic pollution problems include adsorption, membrane filtration, flocculation, reverse osmosis, coagulation sedimentation oxidation-reduction, advanced oxidation degradation, phytoremediation, microbial remediation, etc. The adsorption method has the advantages of simple operation, high removal efficiency, low energy consumption, no secondary pollution, good economic benefits, and recyclability. Therefore, the adsorption method is widely used in dealing with antibiotic pollution. Polymer adsorbent materials have a porous structure and a large surface area, which can effectively adsorb target substances; by regulating the structure and functional groups of the polymer, the adsorption characteristics can be adjusted and optimized. Chitosan is a natural polymer adsorption material containing hydroxyl and amino groups, which can provide active adsorption sites and is conducive to the adsorption of pollutants; chitosan also has good biocompatibility and environmental friendliness, and is a green adsorption material. A single adsorption material has many limitations in application, but a composite adsorption material can combine the advantages of several materials to achieve high performance and low cost. Summary of the invention
[0004] Purpose of the invention: The purpose of the present invention is to provide a method for preparing chitosan-modified polymethacrylate, so as to solve the problem of how to prepare chitosan-modified polymethacrylate materials. Another purpose of the present invention is to propose the application of chitosan-modified polymethacrylate in adsorbing doxorubicin in water, so as to solve the problem of how to adsorb and remove doxorubicin in wastewater.
[0005] Technical solution: The preparation method of chitosan-modified polymethacrylate described in the present invention comprises the following steps:
[0006] (1) mixing methacrylic acid monomer, a crosslinking agent, an initiator and a pore-forming agent and heating the mixture to react to obtain a polymethacrylate polymer;
[0007] (2) The polymethacrylate polymer, water, glacial acetic acid and chitosan are mixed and heated to react to obtain a chitosan-modified polymethacrylate composite material.
[0008] Preferably, in step (1), the methacrylic acid monomer is a mixture of glycidyl methacrylate and α-methacrylic acid; the crosslinking agent is ethylene glycol dimethacrylate; the initiator is azobisisobutyronitrile; the pore-forming agent is C 5-7 Saturated cyclic alcohols and C 10-14 A mixture of saturated straight chain fatty alcohols.
[0009] Preferably, the mass ratio of glycidyl methacrylate to α-methacrylic acid is 3-5:1; the saturated cyclic alcohol is cyclohexanol, the saturated straight-chain fatty alcohol is dodecanol, and the mass ratio of cyclohexanol to dodecanol is 80-100:5-15.
[0010] Preferably, in step (1), the mass ratio of the methacrylic acid monomer, the crosslinking agent, the initiator and the pore-forming agent is 150-250:100-150:2-6:800-1200.
[0011] Preferably, in step (1), the heating reaction condition is 50-70° C. for 10-14 hours, and after the heating reaction, the product is washed with an alcohol solvent and dried to obtain a polymethacrylate polymer.
[0012] Preferably, in step (2), the mass ratio of polymethacrylate polymer to chitosan is 8-12:1; the heating reaction conditions are 60-70°C for 2-6h, and after the heating reaction, the product is washed with an alcohol solvent and dried to obtain a chitosan-modified polymethacrylate composite material.
[0013] In another aspect of the present invention, the chitosan-modified polymethacrylate composite material prepared by the above preparation method is used to adsorb doxorubicin in water.
[0014] Doxorubicin (DOX) is a cytotoxic antibiotic that not only poses a certain threat to human health, but also causes great harm to the ecological environment. Therefore, removing DOX from wastewater is of great significance. The present invention is based on the good biocompatibility and renewability of polymethacrylate, and the significantly enhanced adsorption effect of modified polymethacrylate on DOX, thereby effectively removing DOX from wastewater.
[0015] Preferably, the above-mentioned application step comprises adding the chitosan-modified polymethacrylate composite material into an aqueous solution of doxorubicin and performing oscillation adsorption.
[0016] Preferably, the concentration of the doxorubicin aqueous solution is 10-90 mg / L, and the pH value is 2-9; the oscillation adsorption time is at least 20 min, and the oscillation rate is 100-300 rpm.
[0017] Preferably, the solid-liquid ratio of the chitosan-modified polymethacrylate composite material to the adriamycin aqueous solution is 5-30 mg: 2-8 mL.
[0018] Beneficial effects: Compared with the prior art, the present invention has the following significant advantages:
[0019] The invention is based on the fact that polymethacrylate has good biocompatibility and renewability, and the modified polymethacrylate has significantly enhanced adsorption effect on DOX, thereby achieving effective removal of DOX in wastewater, and the DOX adsorption rate can reach more than 45%. BRIEF DESCRIPTION OF THE DRAWINGS
[0020] Figure 1 This is a screening result diagram of the amount of adsorbent used;
[0021] Figure 2 This is a screening result diagram of the initial mass concentration of the DOX aqueous solution to be treated;
[0022] Figure 3 This is the screening result diagram of adsorption time;
[0023] Figure 4 This is a screening result diagram of the pH of the DOX aqueous solution to be treated;
[0024] Figure 5 This is the SEM image of chitosan modified polymethacrylate composite material. DETAILED DESCRIPTION
[0025] The technical solution of the present invention is further described below in conjunction with the accompanying drawings.
[0026] Example 1: A method for preparing chitosan-modified polymethacrylate is as follows:
[0027] (1) Preparation of polymethacrylate
[0028] Weigh 160 mg of glycidyl methacrylate (GMA) and 40 mg of α-methacrylic acid (MAA), 123 mg of ethylene glycol dimethacrylate (EDMA) as a crosslinker, 4 mg of azobisisobutyronitrile (AIBN) as an initiator, 900 mg of cyclohexanol and 100 mg of dodecanol as pore-forming agents, and ultrasonicate in a 5 mL centrifuge tube for half an hour. Then put the mixed solution into a 60 ° C oven to react for 12 hours. After the reaction is completed, use methanol to wash the solid product, wash three times, and remove the supernatant by centrifugation. Finally, put the product in a 70 ° C oven to dry for 6 hours, and dry to obtain the product polymethacrylate polymer (poly (GMA-MAA-EDMA)).
[0029] (2) A chitosan-modified polymethacrylate composite material was prepared with a mass ratio of polymethacrylate polymer to chitosan of 10:1, as follows:
[0030] Weigh 0.2g of polymethacrylate polymer in a 5mL centrifuge tube, add 2mL of distilled water, 20μL of glacial acetic acid, 0.02g of chitosan, and ultrasonicate for one hour. Then, put the mixed solution into a 65℃ oven for reaction for 4h. After the reaction, use methanol to repeatedly wash the solid product, and remove the supernatant by centrifugation. Finally, put the product into a 70℃ oven and dry it for 2h to obtain the product chitosan modified polymethacrylate composite material (CS@poly(GMA-MAA-EDMA)). Its microscopic morphology is as follows Figure 5 shown.
[0031] Example 2: A method for preparing chitosan-modified polymethacrylate is as follows:
[0032] (1) Weigh 150 mg of glycidyl methacrylate and 50 mg of α-methacrylic acid, 100 mg of ethylene glycol dimethacrylate (EDMA), 2 mg of azobisisobutyronitrile (AIBN), 800 mg of cyclohexanol and 150 mg of dodecanol respectively in a 5 mL centrifuge tube and ultrasonicate for half an hour. Then put the mixed solution into a 50°C oven to react for 14 hours. After the reaction is completed, the solid product is washed with methanol for three times, and the supernatant is removed by centrifugation. Finally, the product is placed in a 60°C oven to dry for 6 hours, and the product polymethacrylate polymer (poly(GMA-MAA-EDMA)) is obtained by drying.
[0033] (2) Prepare chitosan-modified polymethacrylate composite materials with a ratio of polymethacrylate polymer to chitosan of 8:1 (w / w). Specifically: weigh 0.16g of polymethacrylate polymer into a 5mL centrifuge tube, add 2mL of distilled water, 20μL of glacial acetic acid, 0.02g of chitosan, and ultrasonicate for one hour. Subsequently, the mixture was placed in an oven at 60°C for reaction for 6h. After the reaction, the solid product was repeatedly washed with methanol, and the supernatant was removed by centrifugation. Finally, the product was placed in an oven at 70°C and dried for 2h to obtain the chitosan-modified polymethacrylate composite material (CS@poly(GMA-MAA-EDMA)).
[0034] Example 3: A method for preparing chitosan-modified polymethacrylate is as follows:
[0035] (1) Preparation of polymethacrylate
[0036] Weigh 200 mg of glycidyl methacrylate (GMA) and 40 mg of α-methacrylic acid (MAA), 145 mg of ethylene glycol dimethacrylate (EDMA), 6 mg of azobisisobutyronitrile (AIBN), 1000 mg of cyclohexanol and 50 mg of dodecanol in a 5 mL centrifuge tube and ultrasonicate for half an hour. Then put the mixed solution into a 70 ° C oven to react for 10 hours. After the reaction is completed, use methanol to wash the solid product, wash three times, and remove the supernatant by centrifugation. Finally, put the product in a 70 ° C oven to dry for 6 hours, and dry it to obtain the product polymethacrylate polymer (poly (GMA-MAA-EDMA)).
[0037] (2) A chitosan-modified polymethacrylate composite material was prepared with a polymethacrylate polymer and chitosan in a ratio of 12:1 (w / w). Specifically, 0.24 g of polymethacrylate polymer was weighed into a 5 mL centrifuge tube, 2 mL of distilled water, 20 μL of glacial acetic acid, and 0.02 g of chitosan were added, and ultrasonic treatment was performed for one hour. Subsequently, the mixture was placed in a 70°C oven to react for 2 hours. After the reaction was completed, the solid product was repeatedly washed with methanol, and the supernatant was removed by centrifugation. Finally, the product was placed in a 70°C oven and dried for 2 hours to obtain the chitosan-modified polymethacrylate composite material (CS@poly(GMA-MAA-EDMA)).
[0038] Example 4: Adsorption experiment of DOX by CS@poly(GMA-MAA-EDMA)
[0039] To a centrifuge tube containing 5.0 mL of a DOX standard aqueous solution with a mass concentration of 20 mg / L and a pH value of 9.0, 20 mg of CS@poly(GMA-MAA-EDMA) prepared in Example 1 was added, and oscillation adsorption was performed on an oscillator at a speed of 200 r / min. After adsorption for 180 min, the supernatant was collected after centrifugation for 5 min, and the absorbance was measured at a wavelength of 480 nm.
[0040] Example 5: Optimization of adsorbent usage
[0041] The adsorption effect of CS@poly(GMA-MAA-EDMA) on DOX is affected by the quality of the adsorbent. Therefore, the effect of adsorbent quality on the adsorption effect was studied to explore the optimal adsorbent quality.
[0042] The rest is the same as Example 4, except that: the adsorption experiment was carried out when the mass of the adsorbent was 5 mg, 10 mg, 15 mg, 20 mg, 25 mg and 30 mg respectively and other conditions were the same.
[0043] The results are as follows Figure 1 As shown, Figure 1Where R is the adsorption percentage (%), and its calculation formula is as follows:
[0044]
[0045] q is the adsorption amount at time t (mg / g), and its calculation formula is as follows:
[0046]
[0047] In the above two formulas, C0 and C t are the initial mass concentration of DOX and the mass concentration of DOX at time t, mg / L; V0 is the volume of DOX aqueous solution, mL; m0 is the amount of adsorbent used, g.
[0048] Figure 1 The results show that the adsorption percentage of DOX increases with the increase of the amount of adsorbent, but when the amount of adsorbent exceeds 20 mg, the adsorption percentage approaches the limit. On the contrary, the larger the amount of adsorbent, the less DOX is adsorbed per unit mass of adsorbent. When the amount of adsorbent exceeds 20 mg, the amount of DOX adsorbed per unit mass of adsorbent decreases rapidly due to approaching the limit of the adsorption percentage, indicating that more adsorbents do not play the adsorption function.
[0049] Therefore, when the adsorbent addition amount is 20 mg, the adsorption effect is the best. Finally, 20 mg is selected as the optimal adsorbent mass.
[0050] Example 6: Optimization of the initial mass concentration of the doxorubicin aqueous solution to be treated
[0051] The adsorption effect of CS@poly(GMA-MAA-EDMA) on DOX is affected by the initial mass concentration of DOX. Therefore, the effect of concentration on the adsorption effect was studied to explore the optimal concentration.
[0052] The rest are the same as in Example 4, except that:
[0053] Select DOX standard aqueous solutions with concentrations of 10 mg / L, 20 mg / L, 40 mg / L, 50 mg / L, 60 mg / L, and 80 mg / L, and conduct adsorption experiments under the same other conditions. Figure 2 As shown, Figure 2 In this example, the meaning and calculation formula of R and q are the same as Figure 1 . Figure 2 It shows that under the condition that the amount of adsorbent remains unchanged, the greater the initial DOX concentration, the more DOX is adsorbed per unit adsorbent. However, after the adsorption effect of the adsorbent gradually approaches saturation, continuing to increase the initial DOX concentration will greatly reduce the adsorption removal rate of DOX in the solution.
[0054] When the DOX mass concentration was 20 mg / L, the adsorption effect was the best, and 20 mg / L was finally selected as the optimal mass concentration.
[0055] Example 7: Optimization of adsorption time
[0056] The adsorption effect of CS@poly(GMA-MAA-EDMA) on DOX is affected by the adsorption time. Therefore, the effect of adsorption time on the adsorption effect was studied to explore the optimal adsorption time.
[0057] The rest are the same as in Example 4, except that:
[0058] In the range of 20-180 minutes, under the same other conditions, the adsorption experiment was carried out. The absorbance was measured every 20 minutes. The results are as follows Figure 3 As shown, Figure 3 In this example, the meaning and calculation formula of R and q are the same as Figure 1 When the adsorption time is 180 min, the adsorption effect is the best. Finally, 180 min is selected as the optimal adsorption time.
[0059] Example 8: Optimization of pH of the doxorubicin aqueous solution to be treated
[0060] The adsorption effect of CS@poly(GMA-MAA-EDMA) on DOX is affected by the pH of the aqueous solution.
[0061] The rest are the same as in Example 4, except that:
[0062] The pH of the DOX aqueous solution was adjusted using HCl and NaOH solutions. When other conditions remained unchanged, the pH value of the solution was adjusted to 2-9, and the adsorption experiment was carried out. Figure 4 As shown, Figure 4 In this example, the meaning and calculation formula of R and q are the same as Figure 1 When the pH value of the doxorubicin aqueous solution is 9.0, the adsorption effect is the best.
[0063] Embodiment 9: The rest is the same as Embodiment 4, except that:
[0064] The CS@poly(GMA-MAA-EDMA) prepared in Example 2 was used for adsorption treatment.
[0065] Embodiment 10: The rest is the same as Embodiment 4, except that:
[0066] The CS@poly(GMA-MAA-EDMA) prepared in Example 3 was used for adsorption treatment.
[0067] Comparative Example 1: The rest is the same as Example 4, except that:
[0068] Doxorubicin was replaced with mitoxantrone.
[0069] Comparative Example 2: The rest is the same as Example 4, except that:
[0070] Doxorubicin was replaced with idarubicin.
[0071] Comparative Example 3: The rest is the same as Example 4, except that:
[0072] Doxorubicin was replaced with epirubicin.
[0073] Comparative Example 4: The rest is the same as Example 4, except that:
[0074] The polymethacrylate polymer (poly(GMA-MAA-EDMA)) in Example 1 was used to replace CS@poly(GMA-MAA-EDMA) for adsorption treatment.
[0075] Comparative Example 5: The rest is the same as Example 4, except that:
[0076] The chitosan in Example 1 was used to replace CS@poly(GMA-MAA-EDMA) for adsorption treatment.
[0077] The adsorption effects of the adsorbents in Examples 4, 9, 10 and Comparative Examples 1-3 on aqueous solutions of different anti-tumor drugs were measured, and the results are shown in Table 1:
[0078] Table 1 Adsorption rate of adsorbents on different anti-tumor drug aqueous solutions
[0079] Group Adsorption rate (%) Example 4 46.7 Example 9 45.3 Example 10 44.8 Comparative Example 1 7.3 Comparative Example 2 19.1 Comparative Example 3 13.4 Comparative Example 4 6.6 Comparative Example 5 18.3
[0080] As can be seen from the results in Table 1, the composite adsorbent material prepared by the present invention has a huge difference in adsorption effect on different anthracycline anti-tumor drugs. The material only has a high-efficiency adsorption and removal effect on doxorubicin, and has a poor adsorption effect on other compounds with similar structures. Comparative Examples 4 and 5 are compared with Example 4 to show that chitosan or porous polymer materials alone cannot efficiently adsorb doxorubicin, while the use of chitosan to modify porous polymers can significantly improve the adsorption rate of doxorubicin by the composite adsorbent material.
Claims
1. A method for preparing chitosan-modified polymethacrylate, characterized in that: The steps include: (1) mixing methacrylic acid monomer, a crosslinking agent, an initiator and a pore-forming agent and heating the mixture to react to obtain a polymethacrylate polymer; (2) The polymethacrylate polymer, water, glacial acetic acid and chitosan are mixed and heated to react to obtain a chitosan-modified polymethacrylate composite material.
2. The method for preparing chitosan-modified polymethacrylate according to claim 1, characterized in that: In step (1), the methacrylic acid monomer is a mixture of glycidyl methacrylate and α-methacrylic acid; the crosslinking agent is ethylene glycol dimethacrylate; the initiator is azobisisobutyronitrile; the pore-forming agent is C 5-7 Saturated cyclic alcohols and C 10-14 A mixture of saturated straight chain fatty alcohols.
3. The method for preparing chitosan-modified polymethacrylate according to claim 2, characterized in that: The mass ratio of glycidyl methacrylate to α-methacrylic acid is 3-5:1; the saturated cyclic alcohol is cyclohexanol, the saturated straight-chain fatty alcohol is dodecanol, and the mass ratio of cyclohexanol to dodecanol is 80-100:5-15.
4. The method for preparing chitosan-modified polymethacrylate according to claim 1, characterized in that: In step (1), the mass ratio of the methacrylic acid monomer, the crosslinking agent, the initiator and the pore-forming agent is 150-250: 100-150: 2-6: 800-1200.
5. The method for preparing chitosan-modified polymethacrylate according to claim 1, characterized in that: In step (1), the heating reaction condition is 50-70° C. for 10-14 hours. After the heating reaction, the product is washed with an alcohol solvent and dried to obtain a polymethacrylate polymer.
6. The method for preparing chitosan-modified polymethacrylate according to claim 1, characterized in that: In step (2), the mass ratio of polymethacrylate polymer to chitosan is 8-12:1; the heating reaction conditions are 60-70°C for 2-6h, and after the heating reaction, the product is washed with an alcohol solvent and dried to obtain a chitosan-modified polymethacrylate composite material.
7. Use of the chitosan-modified polymethacrylate composite material prepared by the preparation method according to any one of claims 1 to 6 in the adsorption of doxorubicin in water.
8. The use according to claim 7, characterized in that: The method comprises adding a chitosan-modified polymethacrylate composite material into an aqueous solution of doxorubicin and performing oscillation adsorption.
9. The use according to claim 8, characterized in that: The concentration of the doxorubicin aqueous solution is 10-90 mg / L, and the pH value is 2-9; the oscillation adsorption time is at least 20 minutes, and the oscillation rate is 100-300 rpm.
10. The use according to claim 8, characterized in that: The material-liquid ratio of the chitosan modified polymethacrylate composite material to the adriamycin aqueous solution is 5-30 mg: 2-8 mL.